HOUSE-MUSEUM OF M. AUEZOV IN THE CITY OF CHOLPON-ATА (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article touches upon the life of the world’s famous writer, playwright, scientist,academician of the Academy of Sciences of the Kazakh SSR Mukhtar Omarkhanovich Auezov,who worked and rested at his dacha in Cholpon-Ata in 1950-1960s. Thanks to his efforts, theKyrgyz folk epic “Manas”, having gained wide popularity, has become a symbol of the Kyrgyznation. Today, the dacha of Mukhtar Omarkhanovich Auezov serves as a house-museum and asemi-library. In the article, the author gives a comprehensive overview of the exposition of thehouse-museum. The rich legacy of the writer, preserved in the museum, did not go unnoticed. Theauthor also examines the current appearance of the famous writer’s dacha and reports that it is inpoor condition and needs major repairs.
Keywords: singer, manaschi Sayakbay and Sagimbay, kobyzists, Manas, Issyk kul, Cholpon-Ata.